The wear studies of boron suboxide based cutting tool materials in machining applications - Freemantle, Christopher Stuart (My University, 2010)
The wear characteristics of the first generation of boron suboxide (B6O) based cutting tool materials fabricated from spark plasma sintered B6O/Y2O3/Al2O3 material have been investigated in terms of chemical and abrasive wear when machining compacted graphite cast iron (CGI). Static interaction diffusion couple experiments were conducted at temperatures ranging from 700°C to 1300°C in order to simulate the chemical interaction between the tool material (B6O) and the workpiece material (CGI). The samples were studied using optical microscopy, scanning electron microscopy (SEM) and energy dispersive x-ray spectrometry (EDS) as well as x-ray diffraction (XRD) in order to identify the microstructural and compositional changes as well as determine resulting phases. Interactions observed below 900°C were found to be minimal, with significant chemical interactions occurring at 1100°C and above. Iron boride phases were seen to evolve at the interface of the tool and workpiece materials. Silicon diffusion has been identified as a rapidly diffusing constituent with a tendency to diffuse towards the interface. Due to the formation of various chemical products during the experiments, chemical wear is expected to affect B6O tools at expected machining temperatures. Resistance to oxidation of B6O based materials was examined at 1000°C, revealing a tendency for formation of boric acids on the surface of the material in response to B2O3 formation and reaction with atmospheric moisture. Evaporation of boric acids has been observed to result in a mass loss of the material along with boric acid product crystal formation upon cooling. Turning tests have revealed that the first generation of B6O based cutting tools perform comparably with PcBN at very low cutting speeds, but suffer severe abrasive wear as the cutting speed is increased, due to the need for improvements in tool fabrication and the reduction of material damage and a heat affected zone resulting from laser cutting. Ultrahigh pressure sintered B6O based material was produced but was found to possess a poor microstructure. Computational thermodynamics and phase diagram generation has been successfully compared to experimental results in predicting reaction products and chemical behaviour of the tool materials at machining temperatures.